2008
DOI: 10.1002/jsfa.3461
|View full text |Cite
|
Sign up to set email alerts
|

Texture and colour properties of proteins recovered from whole gutted silver carp (Hypophthalmichthys molitrix) using isoelectric solubilisation/precipitation

Abstract: BACKGROUND: According to an FAO report, carp are the cheapest and by far the most commonly consumed fish in the world. Carp have minimal growth requirements, yet rapid growth rates. Although carp are generally considered unsuitable for human consumption in the USA, they have rapidly started populating major bodies of fresh water in the USA to the extent that commercial processing becomes of interest. However, typical mechanical means of meat recovery from carp are impractical owing to the bony nature of the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
89
3
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 71 publications
(103 citation statements)
references
References 37 publications
10
89
3
1
Order By: Relevance
“…Basic solubilisation usually results in higher protein recoveries than acidic treatments. Protein recovery yields for ISP reported in the literature range between 42% and 90% (Chen & Jaczynski, 2007b;Chen et al, 2009;Kristinsson & Liang, 2006;Nolsoe & Undeland, 2009;Taskaya et al, 2009b). The differences may be attributed to different methods used to determine protein concentration and their recovery yield, fish species, centrifugation force used during ISP and a relative concentration of water-soluble sarcoplasmic proteins.…”
Section: Protein Recovery Yield and Fat Recovery Yieldmentioning
confidence: 85%
See 3 more Smart Citations
“…Basic solubilisation usually results in higher protein recoveries than acidic treatments. Protein recovery yields for ISP reported in the literature range between 42% and 90% (Chen & Jaczynski, 2007b;Chen et al, 2009;Kristinsson & Liang, 2006;Nolsoe & Undeland, 2009;Taskaya et al, 2009b). The differences may be attributed to different methods used to determine protein concentration and their recovery yield, fish species, centrifugation force used during ISP and a relative concentration of water-soluble sarcoplasmic proteins.…”
Section: Protein Recovery Yield and Fat Recovery Yieldmentioning
confidence: 85%
“…Although there was no protein solubilisation step, the pH adjustment to the pI increased oil recovery when compared to the conventional heat-aided oil recovery. Taskaya et al (2009b) reported fat recovery yield ranging from 80% to 95% for whole gutted carp processed with ISP. Kristinsson et al (2005) reported similar fat recoveries and fat reduction in the recovered proteins for catfish fillets.…”
Section: Protein Recovery Yield and Fat Recovery Yieldmentioning
confidence: 96%
See 2 more Smart Citations
“…The moisture, crude protein, lipid and crude ash contents produced from fish fillet were found to be 740.3 g kg −1 , 179.8 g kg −1 , 57.5 g kg −1 and 12.8 g kg −1 , respectively. The proximate composition of silver carp reported in different studies [17,33] indicated some differences, especially for the lipid content and protein.…”
Section: Proximate Compositionmentioning
confidence: 92%